2010
DOI: 10.1089/aid.2010.0140
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Drug Resistance-Associated Mutations in Human Immunodeficiency Virus Type 1 CRF01_AE Integrase Derived from Drug-Naive Thai Patients

Abstract: CRF01_AE is a major subtype of human immunodeficiency virus type 1 (HIV-1) circulating in Southeast Asia, including Thailand. We performed genotypic studies on HIV-1 CRF01_AE integrase derived from plasma samples from drug-naive Thai patients. Direct sequencing of amplified CRF01_AE integrase genes revealed that although no primary mutations associated with drug resistance to integrase inhibitors were detected, at least one secondary mutation was found in 96% of samples. Our results indicate that the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…Previous genotypic studies on HIV-1 integrase revealed that several secondary mutations associated with resistance to integrase inhibitors, including V72I, L74I, E92Q, T97A, V151I, M154I/L, E157Q, V165I, V201I, I203M, T206S, and S230N, were frequently detected in many subtypes and CRFs of HIV-1 derived from drug-naive patients in many countries, including Thailand, Cambodia, Vietnam, and the United States. [9][10][11][12][13] In these reports, drug resistance-associated mutations appeared due to natural polymorphisms at amino acid positions 72, 74,97,112,119,125,128,138,151,153,154,155,156,157,163,165,201,203,206, and 230 of HIV-1 integrase, coinciding with our results. [9][10][11][12][13] In addition to these secondary mutations, 40% (16/40) of the CRF01_AE in this study possessed an unusual tetrapeptide insertion (QNME/A) in the C-terminus of the integrase.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Previous genotypic studies on HIV-1 integrase revealed that several secondary mutations associated with resistance to integrase inhibitors, including V72I, L74I, E92Q, T97A, V151I, M154I/L, E157Q, V165I, V201I, I203M, T206S, and S230N, were frequently detected in many subtypes and CRFs of HIV-1 derived from drug-naive patients in many countries, including Thailand, Cambodia, Vietnam, and the United States. [9][10][11][12][13] In these reports, drug resistance-associated mutations appeared due to natural polymorphisms at amino acid positions 72, 74,97,112,119,125,128,138,151,153,154,155,156,157,163,165,201,203,206, and 230 of HIV-1 integrase, coinciding with our results. [9][10][11][12][13] In addition to these secondary mutations, 40% (16/40) of the CRF01_AE in this study possessed an unusual tetrapeptide insertion (QNME/A) in the C-terminus of the integrase.…”
supporting
confidence: 92%
“…[9][10][11][12][13] In these reports, drug resistance-associated mutations appeared due to natural polymorphisms at amino acid positions 72, 74,97,112,119,125,128,138,151,153,154,155,156,157,163,165,201,203,206, and 230 of HIV-1 integrase, coinciding with our results. [9][10][11][12][13] In addition to these secondary mutations, 40% (16/40) of the CRF01_AE in this study possessed an unusual tetrapeptide insertion (QNME/A) in the C-terminus of the integrase. The C-terminal region of HIV-1 integrase is involved in the dimerization and DNA binding of the enzyme 14 ; therefore, it possibly affects the efficiencies of integrase activity and integrase inhibitors.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These polymorphisms were observed at frequencies similar to those recorded in a recent study from Thailand, a neighboring country whose history of HIV infection is closely intertwined with that of Vietnam. 13 In keeping with previously reported Vietnamese data, 14 the polymorphism L74I/M was also detected among our cohort, in two individuals. The L74M…”
supporting
confidence: 92%
“…In the same way, it has been reported that in the absence of primary mutation, all these secondary mutations had little if any effect on drug susceptibility in vitro, thus suggesting rather a secondary role for viral fitness rescue and/or increasing resistance [ 19 ]. Furthermore many previous genotypic studies on HIV-1 IN in treatment-naïve patients living with various viral subtypes in different countries: England, Spain, South Africa, Sub-Saharan Countries, Thailand, Indonesia and Korea have showed that these differences are natural polymorphisms [ 32 34 , 41 43 ]. According to previous studies, and the fact that INIs have not yet been introduced in Morocco, all secondary and additional mutations identified in this study are also likely natural polymorphisms.…”
Section: Main Textmentioning
confidence: 99%